Theoretical calculation of relative binding affinity in host-guest systems. - Lybrand, T P (1986)
The relative free energy of binding the anions Cl- and Br- to the macrotricyclic receptor SC24 in water has been computed by a computer simulation technique. This result and an incidental result for the relative free energy of hydration of the anions are in excellent agreement with experimental data. The simulation approach to ligand-receptor interactions that is described here has significant potential as a predictive tool in chemistry, biochemistry, and pharmacology.